CROSS-SECTORAL GOVERNANCE: EXAMINING THE FLORIDA INTEGRATED NETWORK FOR DATA EXCHANGE AND RETRIEVAL (FINDER) - Ismail Sahin; Murat Gozubenli (European Scientific Journal, ESJ, 2014)
Complicated public problems have forced public agencies to establish partnerships with different organizations from public, private, and non-profit sectors. Law enforcement agencies have understood that it is not possible to cope with those issues alone anymore and that cooperation is needed because criminals and terrorists operate across bureaucratic and jurisdictional boundaries. In this context, information sharing is one of the most important components of this cooperation. For this purpose, the law enforcement agencies in the state of Florida and University of Central Florida (UCF) have engaged in a partnership known as Florida Integrated Network for Data Exchange and Retrieval (FINDER) to create a statewide data sharing system to combine fragmented and disconnected local databases. In this article, highly successful partnership between Florida law enforcement agencies and UCF was examined as an example of cross-sectoral partnership. The study results suggest that FINDER is a significant response to the historical problem of the lack of information sharing among law enforcement agencies. Interorganizational networks may facilitate development of social networks among staff from different agencies by increasing interactions. In addition, keeping the cost of network operation and membership low is important to build and expand the network. Furthermore, organizations should voluntarily participate in network without any government coercion. According to the study results, systematic effectiveness evaluation is essential to identify to what extent the system achieves its predetermined goals and produce outcomes. Finally, it is important to benefit from the dissemination of the experiences of FINDER across the country.